2019
DOI: 10.1002/jctb.6256
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid electrospun porous fibers of poly(lactic acid) and nano ZIF‐8@C600 as effective degradable oil sorbents

Abstract: BACKGROUND: With the rapid industrial and urbanization development, a large amount of oily wastewater is generated from various sources. It is mutagenic and carcinogenic to human health and seriously affects the ecosystem. In this study PLA/ZIF-8@C600 nanofibers were prepared for oil adsorption. RESULTS: Hybrid nanoparticles (ZIF-8@C600) of carbon black C600 and zeolitic imidazolate framework-8 (ZIF-8) with high specific surface area and porous structure were prepared by co-deposition and characterized by scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…47 Further increases of PHB-di-rub to 5% and 10% show a reduction in both modulus and strength; this may be ascribed to the plasticizing effect due to the increase in the rubber ratio in each nanofiber. 46 To the best of our knowledge, the reported tensile modulus and strength are the highest among such a fully biodegradable nanofibrous structure used as oil sorbent, 40,42 even outperforming a non-biodegradable fibrous mat (TS = 0.8−2.01 MPa) that was reported. 8 This mechanical robustness could potentially contribute to the reusability of a sorbent.…”
Section: ■ Results and Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…47 Further increases of PHB-di-rub to 5% and 10% show a reduction in both modulus and strength; this may be ascribed to the plasticizing effect due to the increase in the rubber ratio in each nanofiber. 46 To the best of our knowledge, the reported tensile modulus and strength are the highest among such a fully biodegradable nanofibrous structure used as oil sorbent, 40,42 even outperforming a non-biodegradable fibrous mat (TS = 0.8−2.01 MPa) that was reported. 8 This mechanical robustness could potentially contribute to the reusability of a sorbent.…”
Section: ■ Results and Discussionmentioning
confidence: 80%
“…In another recent work, Wang and co-workers developed a series of PLA membranes incorporated with carbon black C600 and zeolitic imidazolate framework-8 (ZIF-8@C600) that improved hydrophobicity and oil sorption due to high specific surface area and porous structure. 40 Collectively, the establishment of mechanical performance relating to the durability and reusability of these PLA sorbent materials was not extensively discussed, and high oil adsorption−desorption consistency for at least 10 cycles was not achieved. 26,41−43 In this work, we successfully develop a fully biodegradable and highly toughened PLA electrospun nanofibrous membrane incorporated with the designed PHB-based rubber fillers, achieving a membrane with rough topography and low surface energy.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of adsorbents were widely used in the ecosystem and brought with them various disadvantages. There are some disadvantageous situations that still need to be overcome, such as secondary environmental pollution from complex production processes and post-use waste [1].…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Unlike dispersants, the benefits of using sorbents, which included simplicity in application and cost-friendliness, are now of interest to researchers as a remedy for oil spills. [28][29][30][31] Several studies have reported that sorbents with high-performance can easily be obtained by precise tuning of a sorbent's hydrophobicity and swelling capacity. [32,33] Modified sorbents with diverse morphologies, [34][35][36] wettability, [37][38][39][40][41] and specific surface area functions have generated to exploit high oil sorption capacity and reusability, [42][43][44][45][46][47] and these modified sorbents are now playing an important role in oil spill remediation.…”
mentioning
confidence: 99%